Structural and Electrical Properties of Silica Materials from Rice Husks - Casnan; Purnawan; Erliza Noor; Hartrisari Hardjomidjojo; Irzaman; Eti Rohaeti; Aditya Kurniawan (ASEAN Journal on Science and Technology for Development, 2021)
This study aimed to analyze the structural and electrical properties of silica from rice husks recovered by the process of ashing on a medium-scale furnace with a capacity of 15 kg. Rice husks were burned at a heating rate of 1.5°C/min to a temperature of 900°C, where the temperature was retained for 1 hour each at 400°C and 900°C. The methodology of this research was conducted through the process of ashing, extraction of silica, and characterization of its structural electrical properties. The silica extracted from rice husk ash had a relatively low water content by the low absorption intensity of the group –OH at 3610 cm-1. The silica was dominated more by the siloxane group (Si-O-Si) compared with the silanol group (Si-OH). Based on XRD analysis, the silica structure was confirmed as tetragonal. The silica also had a decreased resistance, impedance, and inductance as the frequency increased. These results indicate that the obstacles contained in silica content decrease with an increase in frequency. The decreasing of dielectric constants was caused by the frequency affecting the capacitance; i.e., increased frequency caused more waves to be transmitted each second. The electric current was turned before the capacitor plate was fully charged, which caused quick charge drainage in the capacitor plate and therefore reduced the ability of a material to store the electric charge.